2021
DOI: 10.1111/coa.13702
|View full text |Cite
|
Sign up to set email alerts
|

Stapler closure versus manual closure in total laryngectomy for laryngeal cancer: A systematic review and meta‐analysis

Abstract: Objective Total laryngectomy (TL) is a life‐saving procedure for individuals with advanced laryngeal cancer and those suffering from recurrence after initial treatment. The present study aimed to evaluate the differences between stapler closure (SC) and manual closure (MC) of the pharynx during TL for patients with laryngeal cancer. Design/Setting A systematic literature search was performed using the PubMed, EMBASE and Cochrane Library databases. The data were analysed using Comprehensive Meta‐Analysis softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
(70 reference statements)
1
12
0
Order By: Relevance
“…Furthermore, patients undergoing stapler closure spend less time in the hospital. We report that those undergoing stapler closure spent less time in the hospital, as is supported by other studies ( 10 , 18 ). Reduced hospital time can contribute to the cost-effectiveness of the stapler.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, patients undergoing stapler closure spend less time in the hospital. We report that those undergoing stapler closure spent less time in the hospital, as is supported by other studies ( 10 , 18 ). Reduced hospital time can contribute to the cost-effectiveness of the stapler.…”
Section: Discussionsupporting
confidence: 89%
“…Some authors reported a higher rate of PCF formation in the MS group, although this was not statistically significant ( 14 , 15 ). Others reported a significantly lower incidence of PCF in the SS group ( 16 , 17 ), which is supported by a recent meta-analysis ( 10 ). These variations could be explained by multiple factors, such as a small sample size, as well as patient characteristics that may impair wound healing, such as DM, smoking history, and prior irradiation.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This closed technique significantly shortens the operation time and hospitalization [49]. Post-operative pharyngeal fistula and other complications occurring after stapling closure were shown to be comparable to, if not better than, those occurring after manual closure [48][49][50][51][52]. No study has confirmed the significant benefit of using stapling closure in salvage total laryngectomy [49].…”
Section: Reconstruction Of the Neopharynxmentioning
confidence: 99%
“…Stapler closure versus manual closure in total laryngectomy for laryngeal cancer: A systematic review and meta-analysis Dear Editor, We read with interest the systematic review and meta-analysis on stapler closure vs manual closure in total laryngectomy for laryngeal cancer. 1 The authors should be congratulated for attempting to answer this important question. However, we believe that the authors' conclusion that "the presented meta-analysis provides current evidence for the use of stapler closure in laryngeal cancer patients undergoing total laryngectomy" cannot be supported based on their meta-analysis.…”
mentioning
confidence: 99%